ANALISIS KINERJA KEUANGAN PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA MASA KABINET INDONESIA BERSATU JILID I DAN II - Galih Wisnu Wardhana; Anton Respati Pamungkas; Imam Nazarudin Latief (LPPM University 17 Agustus 1945 Samarinda, 2019)
Financial performance is the determination of certain measures that can measure the success of a company in generating profits. Efficient company performance, one of wich can be seen from the increase in profits earned by the company, so that in the end will bring a positive impact on government revenue from the taxation sector. The purpose of this study was to obtain empirical evidence about the efficiency of food and beverage companies on the IDX during the United Indonesia Cabinet I and II. The population of this research is the manufacturing companies since 2005 -201 which amounted to 19 companies, after the purpose of purposive sampling method with the aim of getting samples in accordance with the research objectives, there are 17 companies that fit the criteria set for the sample. The results of this study prove that there are significant differences for the variables CR, DER, NPM, ROA and EPS, food and beverage companies in the period of KIB I and KIB II, this means that company managers and investors generally responded in the governance period of KIB I and KIB II